1998
DOI: 10.1159/000022449
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of a Portable Monitor for Prothrombin Time Determination, Coaguchek<sup>®</sup>, with Three Systems for Control of Oral Anticoagulant Treatment

Abstract: Self-testing of oral anticoagulation is a new possibility related to the development of portable capillary whole blood prothrombin time monitors. The aim of this study was to evaluate one of this monitors, Coaguchek®, with respect to its comparability with our routine prothrombin time determination system, as well as with the reference manual technique and two thromboplastins of high sensitivity, Manchester Reagent and one manufactured in our center, Thromboplastin Bilbao, in a group of patients on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The laboratory that determined PT using the Neoplastine/STA system in citrated venous plasma obtained a similar correlation as that in other studies [13].…”
Section: Discussionsupporting
confidence: 77%
“…The laboratory that determined PT using the Neoplastine/STA system in citrated venous plasma obtained a similar correlation as that in other studies [13].…”
Section: Discussionsupporting
confidence: 77%
“…Technological advances have lead to the development of user-friendly POC analysers that provide good accuracy using smaller blood samples (12). Numerous studies have shown CoaguChek to be a reliable instrument for INR determination in adult patients requiring anticoagulant therapy (13)(14)(15)(16)(17)(18)(19). In comparison, there has only been one study evaluating the clinical effectiveness of CoaguChek compared to venous INR monitoring in children (9).…”
Section: Discussionmentioning
confidence: 99%
“…The European Concerted Action on Anticoagulation (ECAA) among others have recommended an external calibration of the ISI value [46,50,74,76,[110][111][112]. It is possible to calibrate the CoaguChek R coagulometer using fresh, citrated plasma [75] and even lyophlized plasma [112].…”
Section: Calibrationmentioning
confidence: 99%